2013
DOI: 10.1089/ars.2012.4889
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm Connections to Oxidative Stress: Implications for Human Health

Abstract: Significance: Oxygen and circadian rhythmicity are essential in a myriad of physiological processes to maintain homeostasis, from blood pressure and sleep/wake cycles, down to cellular signaling pathways that play critical roles in health and disease. If the human body or cells experience significant stress, their ability to regulate internal systems, including redox levels and circadian rhythms, may become impaired. At cellular as well as organismal levels, impairment in redox regulation and circadian rhythms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
192
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(214 citation statements)
references
References 201 publications
5
192
0
2
Order By: Relevance
“…Circadian rhythms and OS are further connected by the role they both play in several different diseases. 2 However, in-depth studies have not been done to determine the cause-and-effect relationship between circadian rhythm, OS, and diseases. As well as epiphysis, many other organs synthesize smaller amounts of melatonin, including skin, gastrointestinal tract, liver, kidney, brain, retina, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythms and OS are further connected by the role they both play in several different diseases. 2 However, in-depth studies have not been done to determine the cause-and-effect relationship between circadian rhythm, OS, and diseases. As well as epiphysis, many other organs synthesize smaller amounts of melatonin, including skin, gastrointestinal tract, liver, kidney, brain, retina, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments on animals found that intake of low doses of cadmium (100 ppm) with drinking water in the early stages of intoxication is accompanied by an increase in non-REM sleep against decrease in locomotor activity during wakefulness [22]. These changes in the structure of sleep have been associated with oxidative stress that, according to the authors, is the basis of violations of the sleep-wakefulness cycle [25]. If we consider the data on the important role of the hypothalamic-pituitary system in the organization of rhythms [7] and toxic action of cadmium on it [21,22], the involvement of this system in the violations of daily fluctuations of hormones becomes apparent.…”
Section: Internal Diseasesmentioning
confidence: 99%
“…A very recent growing body of evidence suggests a close connection between the cellular circadian and redox systems (Tamaru et al, 2013;Wilking et al, 2013). Disruption of the circadian clock results in increased oxidative stress and premature senescence both in vitro and in vivo (Kondratov et al, 2006;Khapre et al, 2011).…”
Section: Introductionmentioning
confidence: 99%